Waters of resistance: decolonising perspectives on women's territorial r-existence in southern Chile - Hernando-Arrese, Maite; Ibarra, María Ignacia (Gender and development, 2025)
This article explores the gendered experiences of, and responses to, processes of water commodification and scarcity in rural areas of the Toltén River in southern Chile through a decolonial lens. Within the framework of neoliberal water governance, water use rights are primarily owned by large-scale agribusiness and industrial companies, leading to significant socioecological conflicts (dispossession, pollution, and resource depletion) and gendered disparities in rural areas. Women face severe vulnerability concerning access to land and water rights, often resulting in their exclusion from decision-making processes. Consequently, they encounter barriers to accessing credit, subsidies, and capital, further exacerbating their marginalisation and impoverishment. Drawing upon stories collected from women leaders of rural drinking water committees and co-operatives, social movements, and peasant women in the Toltén hydrosocial territory in southern Chile, we analyse conflicts over water use and valuation, along with the different forms of r-existence in which women engage to counter the commodification of water through community-based water management initiatives. Their efforts challenge portrayals of rural women as passive victims of development and reject the notions of water as a mere resource for exploitation. We argue for the adoption of a decolonial feminist approach to investigate everyday forms of r-existence that contribute to collaborative water governance processes. By centring the diverse needs, concerns, and priorities of rural women, this framework offers pathways for transformative change at the intersection of gender, water governance, and colonial legacies.